Peranan Objek Wisata Mooi Park Dalam Menambah Pendapatan Masyarakat Di Kelurahan Saoka Kota Sorong Provinsi Papua Barat Daya - Alicia Margareicher Tinungki; Ita Pingkan F. Rorong; Krest D Tolosang (PT. Hasba Edukasi Mandiri, 2025)
Mooi Park is one of the tourist attractions that is developing in Saoka, Sorong City, Southwest Papua, and has great potential to improve the economy of the local community. This research aims to analyze the role of the Mooi Park tourist attraction in increasing the income of the surrounding community.The method used is a qualitative descriptive approach with data collection techniques through observation, interviews and documentation. The research results show that the existence of Moooi Park has a positive impact on the economy of the community around the Mooi Park tourist attraction through various sectors, such as increasing business opportunities in the fields of tourism services and trade. Apart from that, the existence of this tourist attraction also creates new jobs that support improving the welfare of the surrounding community. With support from the government and tourism managers, Mooi Park has the potential to become a leading destination.